Роль OAI-PMH в роботі електронних архівів кваліфікаційних робіт - Марковець, Олексій (Видавництво Львівської політехніки, 2025)
This paper explores the role of the OAI-PMH (Open Archives Initiative Protocol for Metadata Harvesting) in the functioning of electronic archives of theses and dissertations. It highlights the protocol’s importance in enabling standardized metadata exchange, interoperability, and integration of institutional repositories into global scholarly networks. Special attention is given to platforms such as DSpace and EPrints, which support OAI-PMH and are widely used in academic institutions. The paper also examines the role of international services like NDLTD and OATD in harvesting metadata via OAI-PMH, thereby enhancing the visibility, accessibility, and long-term preservation of electronic academic works worldwide.
Keywords: кваліфікаційна робота; електроний архів; NDLTD; OATD; EPrints; DSpace; ETD; OAI-PMH